Perspectives of patients on pharmacotherapeutic follow-up in Primary Health Care in a Brazilian capital (Research, Society and Development, 2021)
The pharmaceutical profession has become in the last decades, from a technicist training to a person-centered care. The clinical performance of the pharmacist in Primary Health Care is still incipient and seeks to consolidate by providing pharmacotherapeutic follow-up, whose objective is to identify, prevent and solve drug-related problems. Aiming to know the user's perception regarding pharmacotherapeutic follow-up, a case study qualitative, descriptive interpretative was carried out between January and March of 2017. Twelve users in pharmacotherapeutic follow-up were interviewed individually. From the content analysis emerged two categories: Pharmaceutical-patient relationship and its importance in pharmacotherapy and Positive results in pharmacotherapy result in patient satisfaction. A relationship of trust and co-responsibility between the pharmacist-patient was evidenced. The patient sees the pharmacist as guiding and encouraging in the treatment process, as he considers the individual fully and as the main actor in making decisions about his treatment and health. Users were satisfied with pharmacotherapeutic follow-up, desiring their continuity.